2011
DOI: 10.1080/07448481.2010.515632
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationships Between Resilience, Mental Health, and Academic Persistence in Undergraduate College Students

Abstract: The demands in college are significant and there is a need for more research on the concept of resilience as it relates to college health and academic persistence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
139
0
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(159 citation statements)
references
References 51 publications
8
139
0
12
Order By: Relevance
“…This finding is compatible with that of Siriwardhana et al (2014) and Hartley (2011) (44,45). Resilience is the capacity of an individual to demonstrate psychological health in a situation in which society views it as aversive (46).…”
Section: Discussionsupporting
confidence: 87%
“…This finding is compatible with that of Siriwardhana et al (2014) and Hartley (2011) (44,45). Resilience is the capacity of an individual to demonstrate psychological health in a situation in which society views it as aversive (46).…”
Section: Discussionsupporting
confidence: 87%
“…In addition, PsyCap positively correlated with school adjustment, indicating that individuals with higher levels of PsyCap would adjust to schools more easily. For example, Hartley (2011) found that intrapersonal resilience, an important dimension of PsyCap, contributed to academic persistence. Beauvais et al (2014) also proved that resilience was strongly associated with academic success in graduate nursing students.…”
Section: Discussionmentioning
confidence: 99%
“…Para ellos, sus trayectorias educativas y vitales se encontraron marcadas por obstáculos y situaciones que debían ir solventando y, pese a que consiguieron los objetivos establecidos, el trabajo que tuvieron que realizar para ello fue duro y largo en el tiempo. Por lo que, su proceso de resiliencia se basó en la creación de estrategias de adaptación, organización y estudio como fundamentales para adaptarse al contexto universitario, en ocasiones adverso (Ewert & Yoshino, 2011;Hartley, 2011;Sandín et al, 2014).…”
Section: Discussionunclassified